Answer:
Option (D)
Step-by-step explanation:
Given equation is,
![8e^{2x+1}=4](https://tex.z-dn.net/?f=8e%5E%7B2x%2B1%7D%3D4)
Taking natural log on both the sides of the equation,
![\text{ln}(8e^{2x+1})=\text{ln}(4)](https://tex.z-dn.net/?f=%5Ctext%7Bln%7D%288e%5E%7B2x%2B1%7D%29%3D%5Ctext%7Bln%7D%284%29)
![\text{ln}(2^3)+\text{ln}(e^{2x+1})=\text{ln}(2^2)](https://tex.z-dn.net/?f=%5Ctext%7Bln%7D%282%5E3%29%2B%5Ctext%7Bln%7D%28e%5E%7B2x%2B1%7D%29%3D%5Ctext%7Bln%7D%282%5E2%29)
3ln(2) + (2x + 1)[ln(e)] = 2ln(2)
2n(2) - 3ln(2) = (2x + 1)
2x = -ln(2) - 1
[Since, -ln(2) = ln(1) - ln(2) =
]
![2x=\text{ln(0.5)}-1](https://tex.z-dn.net/?f=2x%3D%5Ctext%7Bln%280.5%29%7D-1)
![x=\frac{\text{ln(0.5)-1}}{2}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B%5Ctext%7Bln%280.5%29-1%7D%7D%7B2%7D)
Therefore, Option (D) will be the correct option.